FAKTOR– FAKTOR YANG MEMPENGARUHI MAHASISWA DALAM MEMILIH MATA KULIAH AKUNTANSI SYARIAH SEBAGAI MATA KULIAH PILIHAN - Rini Mirayanti; Rossje V. Suryaputri; Nia Susnita Sari (Jurnal Akuntansi Trisakti, 2017)
This study aims to examine the factors that affect the interests of students in choosing courses sharia accounting as elective courses. This study uses a modified model Theory of Planned Behavior (TPB) which test relationship attitude with interest, subjective norms with interest, behavior control perceived interests and add construct another, which is the spiritual motivation with interest and consideration of the labormarket by student interest in choosing accounting sharia as elective courses. This study uses survey data collection. Samples from this study are students who are still active academic year 2015/2016 S1 majoring in Accounting and Business class of 2012 and 2013 in the Trisakti University, Mercu Buana University, and the University of Esa Unggul. A total of 110 respondents of data that can be processed by using SPSS 20. The results showed that the variables attitude, subjective norms, spiritual motivation, labor market consideration, and perceived behavioral control positive effect on student interest in choosing sharia accounting as elective courses.